Criminalization of Fraud Victims in Gold Trading Disputes: An Analysis of Conflicting Criminal and Civil Court Decisions in Indonesia - Yuli Maria Lyanawati; M.Syahrul Borman; Vieta Imelda Cornelis (PT. Anagata Sembagi Education, 2026)
The expansion of criminal law into private commercial disputes has raised serious concerns regarding over-criminalization and legal certainty. This article examines the phenomenon of fraud victim criminalization in gold trading disputes through an analysis of conflicting civil and criminal court decisions in Indonesia. Using a qualitative doctrinal and socio-legal case study approach, the study analyzes judicial reasoning in parallel proceedings arising from identical transactional facts. The findings reveal that a purchaser legally recognized as a fraud victim in binding civil judgments was subsequently prosecuted and convicted under corruption and money laundering statutes. This outcome resulted from the disregard of prior civil findings, expansive interpretations of state loss, and a narrow application of the ne bis in idemprinciple. The study argues that such judicial fragmentation undermines legal certainty and distorts the function of criminal law as ultima ratio. By situating the case within theories of over criminalization and miscarriage of justice, this article contributes to the literature on economic crime enforcement and judicial coherence. It concludes by emphasizing the need for stronger doctrinal coordination between civil and criminal adjudication to prevent victim criminalization and ensure fair and consistent application of the law in Indonesia